A novel design of proton computed tomography detected by multiple‐layer ionization chamber with strip chambers: A feasibility study with Monte Carlo simulation. Issue 2 (2nd December 2019) - Chen, Xinyuan; Liu, Ruirui; Zhou, Shuang; Sun, Baozhou; Reynoso, Francisco J.; Mutic, Sasa; Zhang, Tiezhi; Zhao, Tianyu
Abstract : Purpose: Uncertainty in proton range can be reduced by proton computed tomography (CT). A novel design of proton CT using a multiple‐layer ionization chamber with two strip ionization chambers on the surface is proposed to simplify the imaging acquisition and reconstruction. Methods: Two strip ionization chambers facing the proton source were coupled into a multiple‐layer ionization chamber (MLIC). The strip chambers measured locations and lateral profiles of incident proton beamlets after exiting the imaging object, while the integral of depth dose measured in the MLIC was translated into the residual energy of the beamlet. The simulation was performed at five levels of imaging dose to demonstrate the feasibility and performance expectations of our design. The energy of the proton beamlet was set to 150 ± 0.6 MeV. A collimator with a round slit of 1 cm in diameter was placed in the central beam axis upstream from steering magnets. Proton stopping power ratio (SPR) was reconstructed through inverse radon transform on sinograms generated with proton beamlets scanning through an imaging phantom from a half‐circle gantry rotation. The imaging phantom was 10 cm in diameter. The base was made of water‐equivalent material holding 13‐tissue equivalent inserts constructed according to ICRP 1975 (Task Group on Reference Man. "Report of the Task Group on Reference Man: A Report", Pergamon Press 23, 1975). All inserts were 1 cm in diameter with materials ranging from lung to cortical bone. Percentage discrepancies were reported by comparing to the ground truths. The imaging dose and quality were also evaluated. Results: The maximum deviation in reconstructed proton SPR from the ground truths was reported to be 1.02% in one of the 13 inserts when the number of protons per beamlet passing through the slit dropped to 10 3 . Imaging dose was correlated linearly to incident protons and was determined to be 0.54 cGy if 5 × 10 2 protons per beamlet were used. Imaging quality was acceptable for planning purpose and held consistently through all levels of imaging dose. Spatial resolution was measured as five line pairs per cm consistently in all simulations varying in imaging dose. Conclusions: Proton CT using a multiple‐layer ionization chamber with two strip ionization chambers on the surface simplifies data acquisition while achieving excellent accuracy in proton SPR and acceptable spatial resolution. The imaging dose is lower compared to kV CBCT, making it potentially a great tool for localization and plan adaption in proton therapy.